Respons Ulat Hongkong (Tenebrio molitor) terhadap Campuran Media Pakan yang Berbeda - Maria Erviana Kusuma; Gunawan Gunawan; Citra Karmila (Fakultas Peternakan Universitas Kristen Palangka Raya, 2022)
This study aims to determine the effect of mixture of feed media on the production Tenebrio larva and to determine the mix of feed media that can give the best results to the production of Tenebrio larva. This research was conducted at the Laboratory of the Faculty of Animal Husbandry, Palangka Raya Christian University. This research was conducted using a completely randomized design (CRD) with treatment A (50% tofu pulp, 30% cassava flour and 20% rice bran) treatment B (40% tofu pulp, 40% cassava flour and 20% rice bran) treatment C (tofu 30%, cassava flour 50% and rice bran 20%) each treatment was repeated 6 times so that there were 18 experimental units. Parameters observed were body length, body weight and mortality. The results showed that the feeding media mixture had no effect on the production of Hong Kong caterpillar (Tenebrio molitor). Keywords: Mixture, media, feed